Emissions of VOCs From Polymer-Based Consumer Products: From Emission Data of Real Samples to the Assessment of Inhalation Exposure - Morgane Even; Mathilde Girard; Anna Rich; Christoph Hutzler; Andreas Luch (Frontiers Media S.A., 2019)
The development of consumerism led to an increase in toy production. Such consumer products may contain non-intentionally added toxic substances that can emit from the product and may be inhaled by the consumer. Little data is available on the inhalation exposure of humans to volatile organic compounds (VOCs) from consumer products, so a reliable exposure assessment is needed. Only the emission chamber technique developed for building material emissions can provide solid estimations as it allows the products to be studied under real room conditions. This paper proposes a strategy to interpret emission experiment results from consumer products and assess the corresponding potential risk. It focuses on 14 common VOCs. The identification of the polymer type of 41 plastic articles was first performed by pyrolysis coupled online to gas chromatography with mass spectrometric detection (pyr-GC/MS). Their VOC profile was also determined by Dynamic Headspace-GC/MS (DHS-GC/MS). Softer polymers caused higher and broader emission profiles. Four specific toy samples were selected to be studied in a 203 l emission chamber and their emissions were compared to a reference material. A rapid decrease in the emissions was observed for each product and VOC. Based on these emission curves over time, the corresponding indoor air concentration could be calculated for the target VOCs for short-term or long-term exposures. The indoor air levels obtained were at least 35 times lower than the levels according to conventional indoor air guidelines. Guideline values were only exceeded using very conservative exposure scenarios.